2022
DOI: 10.1080/13880209.2022.2069823
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin suppressed the migration, invasion, epithelial mesenchymal transition (EMT) and lung metastasis of colorectal cancer cells by down-regulating ADRB2 expression

Abstract: Context Cardamonin (CDN) can suppress cell growth in colorectal cancer (CRC), a common digestive malignancy. Objective We explored the effect and mechanism of CDN on metastatic CRC. Materials and methods Two cell lines (HT29 and HCT116) were initially treated with CDN at different concentrations (5, 10 and 20 μmol/L) or 50 μmol/L propranolol (positive control) for 24 or 48 h. Then, the two cell lines were separately transfected with siADRB2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Additionally, several other enzymes have been identified as targets for chalcones, including aurora kinases [ 116 , 117 ], cyclooxygenases (COXs), 5-lipoxygenase [ 96 , 118 ], hexokinases II [ 119 ], matrix metalloproteinases [ 120 , 121 ], various tyrosin kinases [ 122 , 123 ] and NO synthase [ 124 ].…”
Section: Molecular and Cellular Mechanisms Of Actionmentioning
confidence: 99%
“…Additionally, several other enzymes have been identified as targets for chalcones, including aurora kinases [ 116 , 117 ], cyclooxygenases (COXs), 5-lipoxygenase [ 96 , 118 ], hexokinases II [ 119 ], matrix metalloproteinases [ 120 , 121 ], various tyrosin kinases [ 122 , 123 ] and NO synthase [ 124 ].…”
Section: Molecular and Cellular Mechanisms Of Actionmentioning
confidence: 99%
“…Subcutaneous xenograft experiments have demonstrated it to be highly tumorigenic. Therefore, it is currently widely used in the study of colorectal cancer metastasis [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, researchers investigated the molecular mechanism of CDN in inhibiting lung metastasis in CRC and its potential as a therapy for CRC patients [ 40 ]. They found that CDN effectively suppressed ADRB2 expression, leading to reduced viability, migration, invasion, and EMT in CRC cell lines (HT-29 and HCT116).…”
Section: Anticancer Activity Of Chalcones Against Colon Cancermentioning
confidence: 99%
“…They found that CDN effectively suppressed ADRB2 expression, leading to reduced viability, migration, invasion, and EMT in CRC cell lines (HT-29 and HCT116). These in vitro findings were validated in a mouse metastasis model, highlighting CDN’s promise as a therapy for lung metastasis in CRC patients [ 40 ]. The study also revealed that EMT, a process that is crucial for cancer metastasis, involved the regulation of key markers such as E-cadherin, N-cadherin, MMP-2, and MMP-9, all of which were influenced by CDN treatment.…”
Section: Anticancer Activity Of Chalcones Against Colon Cancermentioning
confidence: 99%